Managing people in entrepreneurial organizations learning from the merger of entrepreneurship and human resource management - Katz, Jerome A.; Welbourne, Theresa M. (Amsterdam ; Boston : JAI, 2002)
The last years of the 20th Century may well have reflected a brief golden age for human resource management. In an economy where ideas and capital were plentiful, the critical facet for success increasingly became human resources. Having the people on hand, with the right skills to bring new products into existence with a first mover advantage became the definitive factor. As a result, policies and initiatives at the intersection of entrepreneurship and human resource management proliferated in an unprecedented way, and is the focus of this volume. As is traditional for this series, the volume includes two major reviews: of HRM in entrepreneurship and of stock related rewards. The volume also includes papers on topics emerging from the retrospective of the dot-com boom and bust, such as optimal methods of recruitment for smaller firms, defining and assessing the new concept of person-entrepreneurship fit, and the impact of union relationships on small high-performance firms.
Performance in fast growth firms : the behavioral and role demands of the founder throughout the firm's development / Diane E. Johnson, Karen Bishop -- Stock-related rewards, social identity, and the attraction and retention of employees in entrepreneurial SMEs / Mary E. Graham, Brian Murray, Linda Amuso -- Performance and growth in entrepreneurial firms : revisiting the union-performance relationship / Rosemary Batt, Theresa M. Welbourne -- Individual differences and the pursuit of new ventures : a model of person-entrepreneurship fit / Gideon D. Markman, Robert A. Baron -- Human resource management models for entrepreneurial opportunity : existing knowledge and new directions / Robert L. Heneman, Judith W. Tansky -- Smaller but not necessarily weaker : how small businesses can overcome barriers to recruitment / Ian O. Williamson, Daniel M. Cable, Howard E. Aldrich -- Introduction : human resource management in entrepreneurial settings : towards a relational approach / Theresa M. Welbourne, Jerome A. Katz.
Includes bibliographical references.
Description based on print version record.
Keywords: Personnel management; Entrepreneurship; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management